PENGGUNAAN METODE CHISANBOP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN PAKUJAYA 02 TANGERANG - ANASTASIA BARBARA SUTARTI (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2021)
The aims of this study were 1) to increase students' motivation and numeracy skills, 2) to improve students' mathematics learning outcomes through the chisanbop method. This type of research is Classroom Action Research (CAR). The subjects of this study were fourth grade students of SD Negeri Paku Jaya 2, Tangerang, Banten. The object of this research is the implementation process of learning to count using the chisanbop method. This Classroom Action Research was carried out in 3 cycles. The research data was collected by using the methods of tests, observations, interviews, questionnaires and documentation. The implementation of numeracy learning using the chisanbop method which can increase students' motivation, activity and numeracy skills is carried out by the teacher demonstrating how to count with the chisanbop equipped with the use of chisanbop teaching aids. Students observe and demonstrate what is demonstrated and exemplified by the teacher. The results of this study are 1) increasing students' motivation and activity can be seen when learning mathematics. In the first cycle, 77%, the second cycle increased to 78.3% and the third cycle to 89.58%. 2) the increase in students' mathematics learning ability can be seen in the first cycle, with an average of 56.30 increasing in the second cycle to 72.29 and the third cycle, 82.63. The percentage increase in learning outcomes in cycle II was 28.4% from cycle I, and in cycle III increased by 46.76% from cycle I, increased by 14.30% from cycle II. Based on the results of these studies, it can be concluded that to determine the increase in numeracy skills and increase motivation to learn mathematics in fourth grade students of SD Negeri Paku Jaya 2, Tangerang, Banten, through the Chisanbop method. ABSTRAKTujuan dari penelitian ini adalah 1) meningkatkan motivasi, dan keterampilan berhitung siswa, 2) meningkatkan hasil pembelajaran matematika siswa melalui metode chisanbop. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek dari penelitian ini adalah siswa kelas IV SD Negeri Paku Jaya 2, Tangerang, Banten. Objek dari penelitian ini adalah proses pelaksanaan pembelajara berhitung menggunakan metode chisanbop. Penelitian Tindakan Kelas ini dilaksanakan dalam 3 siklus. Pengumpulan data penelitian dilakukan dengan metode tes, observasi, wawancara, angket dan dokumentasi. Pelaksanaan pembelajaran berhitung dengan menggunakan metode chisanbop yang dapat meningkatkan motivasi, aktivitas dan kemampuan berhitung siswa dilaksanakan dengan cara guru mendemonstrasikan cara berhitung dengan chisanbop dilengkapi dengan penggunaan media alat peraga chisanbop. Siswa mencermati dan memperagakan apa yang diperagakan dan dicontohkan oleh guru. Hasil dari penelitian ini adalah 1) meningkatkan motivasi dan aktivitas siswa dapat dilihat pada saat pembelajaran matematika. Pada siklus I, 77%, siklus II meningkat menjadi 81% dan siklus III menjadi 89,58%. 2) peningkatan kemampuan belajar matematika siswa dapat dilihat pada siklus I, dengan rata-rata 56,30 meningkat pada siklus II menjadi 72,29 dan siklus III, 82,63. Persentase peningkatan hasil belajar pada siklus II sebesar 28,4% dari siklus I, dan pada siklus III meningkat sebesar 46,76% dari siklus I, meningkat sebesar 14,30% dari siklus II. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa untuk mengetahui peningkatan kemampuan berhitung dan peningkatan motivasi belajar matematika siswa kelas IV SD Negeri Paku Jaya 2, Tangerang, Banten, melalui metode Chisanbop.